1988
DOI: 10.1063/1.1140047
|View full text |Cite
|
Sign up to set email alerts
|

Variable-temperature scanning tunneling microscope

Abstract: A thermally compensated tube scanner scanning tunneling microscope (STM) has been constructed and successfully tested. This design utilizes two concentric piezoelectric tubes, one for scanning and one for thermal compensation and inertial sample translation (over several mm), as well as fine adjustment of sample position while in tunneling range. This design eliminates the need for mechanical components such as springs, levers, gears, or stepper motors that are known to result in considerable vibration sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(71 citation statements)
references
References 13 publications
0
70
0
Order By: Relevance
“…Our experiments were conducted using a homebuilt room temperature ultra-high vacuum scanning tunnelling microscope (UHV-STM) at a base pressure of 5×10 -11 Torr [22]. In our experimental setup, the bias voltage is applied to the sample and the tip is grounded through a current preamplifier.…”
Section: Methodsmentioning
confidence: 99%
“…Our experiments were conducted using a homebuilt room temperature ultra-high vacuum scanning tunnelling microscope (UHV-STM) at a base pressure of 5×10 -11 Torr [22]. In our experimental setup, the bias voltage is applied to the sample and the tip is grounded through a current preamplifier.…”
Section: Methodsmentioning
confidence: 99%
“…1(f) we are looking at electrons of decreasing kinetic energy, i.e., we are moving from the elastic peak region of the spectrum through the energy-loss features associated with plasmon and interband excitations 11-17 until we finally reach the low-energy secondary electrons emitted from the surface. We have previously reported images 6,18 in which the total yield of backscattered (and secondary) electrons was recorded while scanning across the surface, and shown that in this case the image contrast depends on shadowing effects and edge enhancement arising from the surface topography. 18 The individual images shown in Fig.…”
Section: Scanning Probe Energy Loss Spectroscopy Below 50 Nm Resolutionmentioning
confidence: 99%
“…The SPELS instrument employed in this study employed a STM head based on the "pocket size" STM design of Lyding and others, [6][7][8] which provides good access to the sample surface. The STM tips were produced by etching a 0.5 mm polycrystalline tungsten wire in a two-molar solution of NaOH; the tips were cleaned in situ by electron bombardment heating, and sharpened by argon ion sputtering.…”
Section: Scanning Probe Energy Loss Spectroscopy Below 50 Nm Resolutionmentioning
confidence: 99%
“…Passivation and STM are performed in an UHV chamber with a background pressure below 1 × 10 − 10 Torr. Scanning and patterning are performed at room temperature in a home-built UHV-STM system 37 . Th e Si(100) 2 × 1:H surface is prepared by overnight degas at 600 ° C followed by three 1,250 ° C fl ashes (30 s, 10 s, 5 s) and passivated by atomic hydrogen generated at a 1,300 ° C tungsten fi lament in a hydrogen background (2 × 10 − 6 Torr).…”
Section: Methodsmentioning
confidence: 99%